2020
DOI: 10.1108/aaouj-06-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Toward a framework for strengthening participants' self-efficacy in online education

Abstract: PurposeThe purpose of this study was to review the role of self-efficacy in online education with an objective to propose a holistic framework for strengthening participants' self-efficacy, especially in the Asian context.Design/methodology/approachTo investigate the potential role of self-efficacy of the participants of online academic activities, this study followed the conceptual analysis method, which is breaking down concepts into constituent elements to get a superior understanding of a particular philos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…Several studies (Boston, 2002 ; Hawkins et al, 2012 ; Kundu, 2018a ; Lazarus, 2003 ; Murphy & Manzanares, 2008 ; Murphy & Rodriguez-Manzanares, 2009 ; Tallent-Runnels et al, 2006 ) have reported that the teachers’ role, pedagogical techniques, and instructional practices, used in face-to-face learning, have to be modified for virtual settings. The selected evidence cautiously suggests that virtual education and online teaching practices can be successfully used to supplement learning if accompanied by appropriate technical environments and support (Kundu, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Boston, 2002 ; Hawkins et al, 2012 ; Kundu, 2018a ; Lazarus, 2003 ; Murphy & Manzanares, 2008 ; Murphy & Rodriguez-Manzanares, 2009 ; Tallent-Runnels et al, 2006 ) have reported that the teachers’ role, pedagogical techniques, and instructional practices, used in face-to-face learning, have to be modified for virtual settings. The selected evidence cautiously suggests that virtual education and online teaching practices can be successfully used to supplement learning if accompanied by appropriate technical environments and support (Kundu, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge, therefore, would have multiplied many-fold for younger children as well as technology-skill-deficient teachers. Lack of concentration, focus, and attention span are anecdotally considered as the more significant risks in a virtual environment that are much exaggerated in younger children(Kundu, 2020a , b ). In order to make online learning effective for children, structured efforts are required to use a range of engagement methods and collaboration tools (Li & Lalani, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In response to school closures, UNESCO recommended the use of online and distance learning programs and open educational applications and platforms that schools and teachers can use to reach learners remotely and limit the disruption of education (UNESCO, 2020e) and several other studies also recommended in this direction (Karp and McGowan, 2020). However, the question arises how far UNESCO guidelines for moving online could be implemented in a developing country such as India where the digital divide is awe-inspiring, digital inclusion and infrastructure for online education is at a lamentable stage, which cannot be rooted out overnight (Kundu, 2020). Several past studies have found a skeletal picture of online education infrastructure in India suffering from numerous shortcomings (Thirumurthy and Sundaram, 2003;Bharadwaj, 2007;Gupta and Haridas, 2012;Prasad, 2013;Netragaonkar, 2015;Bindu, 2019) and this pandemic has highlighted the deep digital divide.…”
Section: Responding Coronavirus Disease 2019 Highlights Digital Dividementioning
confidence: 99%
“…ICTs have brought the globe in a room and made functioning easy and faster (Kundu, 2020a). Similarly, e-assessment has made assessment developed, accurate and faster compared to traditional time-taking paper-based measures (Hillier, 2014; Stodberg, 2012; De Villiers et al , 2016).…”
Section: Advantages Of E-assessmentmentioning
confidence: 99%